The productivity and competency of information technology in upscale hotels The perception of hotel managers in Turkey - DUMANOĞLU, SEZAYİ (EMERALD GROUP PUBLISHING LTD, 2009)
Purpose - This paper aims to examine and analyze the findings of an empirical survey of the productivity of guest-related IT applications and perceptions of hotel managers on IT competency in upscale hotels in Turkey. Design/methodology/approach - The data is collected via a structured questionnaire from 122 upscale hotels in Turkey. Findings - The findings of this study show that hotel managers view guest-related IT applications as highly productive and appreciate IT's benefits. It seems there is a strong relationship between guest-related IT applications and productivity in the lodging industry. Research limitations/implications - This study reflects the perception of hotel managers working in a specific country, i.e. Turkey (and only upper class hotels). Practical implications - This study provides a useful insight for hoteliers to understand the productivity dimensions of guest-related IT applications. This understanding will shape the patterns of decision makers when considering the adoption of certain technologies or when preparing IT capital budgets. The results will also assist hoteliers to adopt the most beneficial technologies and formulate more appropriate strategies around customer preferences. Originality/value - Changes in customer preferences and new innovations leave some technology applications outdated or useless. This study provides a new perspective on the productivity of guest-related IT applications. The findings of this paper can be used as a guide for hoteliers deciding on which IT applications to be implemented to meet customer expectations while maximizing the benefits of a hotel property.
Keywords: Hotels; Communication technologies; Productivity rate; Turkey; FIRM PERFORMANCE; CAPABILITY